Training on Digital Marketing Strategies through Social Media at the Parish of St. Mary Immaculate Conception, Cathedral of the Archdiocese of Medan - Wilianto, W.; Yuliana, Y.; Parulian, Edison; Saragih, Lenny Menara Sari; Lusiah, L. (Golden Ratio of Community Services and Dedication, 2026)
This training aims to provide the congregation of the Cathedral Church of the Archdiocese of Medan with a practical understanding of utilizing social media as a digital marketing tool. With the widespread use of Instagram, Facebook, and WhatsApp Business among the public, this training focuses on branding strategies, content creation, and effective digital promotion techniques for MSMEs. This activity is a collaboration between the Cathedral Church and the Information Technology & Management Study Program of IBBI University and was held on July 20, 2025, in the Van De Hurk Hall. The results of the activity showed an increase in participants' understanding of digital marketing and motivation to market products more professionally through social media platforms.